Exposição perinatal ao preguicida em ratos Wistar: estudo de efeitos toxicológicos sobre a geração e o desenvolvimento da prole - Montanha, Francisco Pizzolato [UNESP] (2015)
This study aimed to evaluate the toxicological effects in rats Wistar exposed to fipronil in the perinatal period. The animals used were acquired from the Biotério Central of UNESP, Botucatu and the tests were performed on their offspring. Were evaluated the physical and sensory-motor development and applied behavioral tests, such as the Open Field test, to assess general activity; the Plus Maze Elevated to assess the anxiety behavior; Hole-Board for motor coordination; tests Recognition New Object and Octagonal Labyrinth, to assess cognitive and spatial memory, respectively; and Aggressivity test, according to the resident/intruder animal paradigm. Were measured levels of Acetylcholinesterase, Cortisol, Alanine aminotransferase and Aspartate aminotransferase by spectrophotometry, and quantified fipronil and metabolites in the brains of rats, by chromatographic analysis. Fragments of organs as brain and liver were collected and evaluated by histopathology technique. According to the results, fipronil alter the physical development, increased anxiety and aggression, impaired memory and motor coordination, induced increase in the Acetylcholinesterase activity, caused histological changes in the brain and liver of these animals. Fipronil is considered toxic to the central nervous system and liver of rats, young and adults, exposed to pesticide in the perinatal period